Évolution de l’environnement alpin - Philippe Schoeneich; Carmen de Jong (Revue de Géographie Alpine)
The way the Alpine environment will evolve in the 21st century depends upon climate change. This could lead to climates never before seen in the Alps, resulting in a major and lasting environmental crisis. In the face of these challenges, funding is still insufficient for specialised research on mountain environments. State funding often prioritises polar research at the expense of high altitude areas, whereas funding schemes from bodies such as Interreg do not sufficiently address the need for fundamental research, which is nevertheless a necessary first step prior to establishing scenarios. Over the last two or three years, there has been some progress towards transalpine network projects. This article identifies the main challenges faced by the alpine environment research field and the capacity of research programmes to meet these needs. The first section, on climate change, is based on the following recent reports: the IPCC 2007 summary report (IPCC 2007), the IPCC Europe report (Alcamo et al. 2007), and the ClimChAlp programme summary report (Prudent-Richard et al. 2008). These contain full, detailed bibliographies. The second section analyses recent or current calls for proposals, and projects which have been selected for funding.